Perkembangan Penyelesaian Sengketa Pertanahan di Luar Pengadilan Melalui Proses Mediasi - Dinda Ayu Putri Septiani; Edith Ratna M.S. (Notarius, 2022)
The Land Office does not only handle or produce certificates but also plays a role in mediation for land dispute resolution. However, the existing rules in regulations with practice in the field often experience disharmony, which hinders mediation. The purpose of writing this journal, among others, is to find out the procedures for the implementation of mediation carried out by the National Land Agency in resolving disputes based on the Regulation of the Minister of Agrarian Affairs regarding Land Case Settlement, this is to find out obstacles that can hinder the implementation of mediation carried out by the National Land Agency in resolving land disputes. The discussion results on writing this journal indicate that the implementation of mediation in resolving land disputes by BPN is said to be successful if the mediation results reach an agreement between the parties. There are obstacles in the implementation of land mediation carried out by BPN. These obstacles can be caused by the parties or by the mediator. Meanwhile, the land dispute mediation conducted by BPN has not all been in accordance with procedures, and there are obstacles in its implementation.Keywords: Non-litigation settlement; Mediation; Land Dispute.AbstrakKantor Pertanahan tidak hanya sekedar menangani atau membuat sertifikat tetapi berperan juga dalam hal mediasi untuk penyelesaian sengketa tanah. Namun aturan yang ada didalam regulasi dengan praktik di lapangan sering mengalami disharmonisasi yang menghambat mediasi. Tujuan penulisan Jurnal ini antara lain untuk mengetahui tata pelaksanaan mediasi yang dilakukan oleh Badan pertanahan Nasional dalam penyelesaian sengketa berdasarkan Peraturan Menteri Agraria tentang Penyelesaian Kasus Pertanahan, hal ini untuk mengetahui kendala yang dapat menghambat pelaksanaan mediasi yang dilaksanakan oleh Badan Pertanahan Nasional dalam penyelesaiang sengketa tanah. Hasil dari pembahasan penulisan jurnal ini menunjukkan bahwa pelaksanaan mediasi dalam penyelesaian sengketa pertanahan oleh BPN dikatakan berhasil jika hasil mediasi mencapai kata sepakat diantara para pihak. Terdapat kendala dalam pelaksanaan mediasi pertanahan yang dilakukan oleh BPN, kendala tersebut bisa disebabkan oleh para pihak ataupun dari mediator. Sementara itu pelaksanaan mediasi sengketa tanah yang dilakukan oleh BPN belum semua sesuai dengan prosedur dan terdapat kendala dalam pelaksanaannya.Kata Kunci : Penyelesaian Non-Litigasi; Mediasi; Sengketa Tanah.